Innovative and sustainable platforms for the downstream processing of antibody-based biopharmaceuticals - Capela, Emanuel Augusto Vieira (2024)
Antibodies, and in particular immunoglobulin G (IgG), are considered as one of the spearheads of the biopharmaceutical industry, presenting high relevance for the treatment of several diseases and being sometimes the only available therapy for some pathologies. Despite their wide potential, the extraction and purification of these biomolecules from their complex biological media with high quality and purity is still based on multi-step approaches and is of high cost. Therefore, the development of alternative and cost-effective downstream processes able to provide high amounts of therapeutic antibodies at lower cost is highly demanded. Novel ionic-liquid-based (IL-based) strategies for the downstream processing of antibodies were investigated in this PhD thesis. ILs were chosen mainly due to their designer solvents character. This feature of ILs allows to tailor the polarity, interactions and selectivity of the developed processes, allowing to overcome some technical limitations of the conventional ones. Three types of IL-based platforms for antibodies downstream processing were investigated, namely aqueous biphasic systems (ABS), three-phase partitioning (TPP) and supported ionic liquids (SILs). ABS containing ILs as adjuvants were investigated, allowing the extraction and purification of human antibodies (polyclonal and monoclonal antibodies) with good performance in a single-step. More biocompatible and sustainable ILs were also studied as phase-forming compounds of ABS, while showing the possibility of using TPP approaches based on ABS for the purification and recovery of human antibodies. Finally, new chromatographic matrices were proposed based on SILs materials, able to capture and/or purify antibodies from their complex biological media through two different mechanisms, namely through the flowthrough-like and bind-and-elute-like modes. In summary, in this PhD thesis it is shown that ILs, if properly designed, can be successfully applied in the extraction, purification and/or recovery of human antibodies, being promising alternative platforms for the downstream processing of antibody-based biopharmaceuticals.